Geospatial web services : advances in information interoperability - Zhao, Peisheng, 1971-; Di, Liping (Hershey, PA : Information Science Reference, 2011)
" This book highlights the strategic role of geospatial Web services in a distributed heterogeneous environment and the life cycle of geospatial Web services for building interoperable geospatial applications"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Geographic information systems; Internet